Impact of Ureaplasma urealyticum infection on semen parameters and in vitro fertilization outcomes in infertile men - Wan, Yangyang; Chen, Xin; Chen, Zhaoyu; Liu, Wenjing; Li, Siyao; Hua, Juan (Frontiers in Endocrinology, 2024)
Introduction Ureaplasma urealyticum (UU) is a common pathogen associated with genital tract infections in infertile males. However, its impact on semen quality, embryo development, and in vitro fertilization (IVF) outcomes remains underexplored. This study aims to evaluate the effect of male UU infection on semen parameters, embryo development, pregnancy outcomes, and neonatal health in infertile couples. Methods A retrospective analysis was conducted on 1,215 infertile couples at the First Hospital of USTC. Participants were divided into two groups based on the male partner’s UU infection status: UU-positive (n=249) and UU-negative (n=966). Semen parameters (sperm concentration, motility, morphology, anti-sperm antibodies, DNA stainability) were assessed. Embryo development was evaluated through fertilization rates and blastocyst formation rates. Pregnancy outcomes (clinical pregnancy, live birth rates, miscarriage rate) and neonatal health (gestational age, birth weight, Apgar scores, preterm delivery) were also compared. Results Semen parameters, including sperm concentration, motility, and morphology, were similar between the UU-positive and UU-negative groups. However, the UU-positive group had significantly higher levels of anti-sperm antibodies (ASA) (p=0.020) and higher DNA stainability (HDS) (p=0.014). Despite these differences, embryo quality, as measured by fertilization rates and blastocyst formation rates, was not significantly different between the two groups. Pregnancy outcomes, including clinical pregnancy and live birth rates, were also comparable. While the UU-positive group had a slightly higher miscarriage rate, this difference was not statistically significant. Neonatal outcomes, including gestational age, birth weight, Apgar scores, and preterm delivery rate, did not differ significantly between the two groups. Discussion The study suggests that while male UU infection may adversely affect certain semen parameters, its impact on IVF outcomes—such as embryo quality, pregnancy rates, and neonatal health—appears to be minimal. These findings support the continued use of IVF as a viable and safe option for infertile couples with male UU infection, as it does not significantly influence reproductive or neonatal outcomes.